Firewall - Ford, Harrison , 1942-; Bettany, Paul , 1971-; Madsen, Virginia , 1963- (Burbank, California : Warner Home Video, 2006)
Special features: Firewall decoded: a conversation with Harrison Ford and Richard Loncraine; 'Firewall': writing a thriller; theatrical trailer. Bank security expert Jack Stanfield specializes in designing infallible theft-proof financial computer systems. But there is a hidden vulnerability in the system he didn't account for - himself. When a ruthless criminal mastermind kidnaps his family, Jack is forced to find a flaw in his system and steal MPAA rating: PG-13; for some intense sequences of violence.
Keywords: Security systems -- United States -- Drama; Security consultants -- United States -- Drama; Kidnapping -- United States -- Drama; Criminal behavior -- United States -- Drama; Sistemas de seguridad -- Estados Unidos -- Teatro; Secuestro -- Estados Unidos -- Teatro; Feature films; Thrillers (Motion pictures, television, etc.); Video recordings for the hearing impaired; Thriller -- Feature; Crime -- Feature; Suspense films